The Role of Merchandise Inventory Management Applications in Strengthening Internal Control Systems of MSMEs: A Case Study - Anugrahani, Inanda Shinta; Purnamasari, Fitri; Muhammad, Muhammad; Azizah, Safira Rusyda; Asmira, Zainah; Darmawan, Novia Ramadhina (Dinasti Publisher, 2026)
Most MSMEs in Indonesia still experience challenges in inventory management, primarily due to manual recording that can potentially lead to data errors and operational inefficiencies. Similar problems are experienced by Toserba HM in Malang Regency, which faces discrepancies between physical stock and system records, as well as difficulties in controlling receivables due to inaccurate recording. The limited utilization of the existing cashier system exacerbates these conditions, necessitating a simple and easy-to-use technology-based solution. This study aims to develop and test the effectiveness of a web application called SIP (Inventory Information System) to improve stock recording accuracy and operational efficiency at Toserba HM. This application is designed with a barcode feature to support real-time inventory recording and monitoring. The results are expected to demonstrate increased inventory management effectiveness and contribute to the application of information technology in strengthening the internal control system of MSMEs in the trade sector.